If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -2(a + -6) = -4 + -3a(a + 5) Reorder the terms: 8 + -2(-6 + a) = -4 + -3a(a + 5) 8 + (-6 * -2 + a * -2) = -4 + -3a(a + 5) 8 + (12 + -2a) = -4 + -3a(a + 5) Combine like terms: 8 + 12 = 20 20 + -2a = -4 + -3a(a + 5) Reorder the terms: 20 + -2a = -4 + -3a(5 + a) 20 + -2a = -4 + (5 * -3a + a * -3a) 20 + -2a = -4 + (-15a + -3a2) Solving 20 + -2a = -4 + -15a + -3a2 Solving for variable 'a'. Reorder the terms: 20 + 4 + -2a + 15a + 3a2 = -4 + -15a + -3a2 + 4 + 15a + 3a2 Combine like terms: 20 + 4 = 24 24 + -2a + 15a + 3a2 = -4 + -15a + -3a2 + 4 + 15a + 3a2 Combine like terms: -2a + 15a = 13a 24 + 13a + 3a2 = -4 + -15a + -3a2 + 4 + 15a + 3a2 Reorder the terms: 24 + 13a + 3a2 = -4 + 4 + -15a + 15a + -3a2 + 3a2 Combine like terms: -4 + 4 = 0 24 + 13a + 3a2 = 0 + -15a + 15a + -3a2 + 3a2 24 + 13a + 3a2 = -15a + 15a + -3a2 + 3a2 Combine like terms: -15a + 15a = 0 24 + 13a + 3a2 = 0 + -3a2 + 3a2 24 + 13a + 3a2 = -3a2 + 3a2 Combine like terms: -3a2 + 3a2 = 0 24 + 13a + 3a2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. 8 + 4.333333333a + a2 = 0 Move the constant term to the right: Add '-8' to each side of the equation. 8 + 4.333333333a + -8 + a2 = 0 + -8 Reorder the terms: 8 + -8 + 4.333333333a + a2 = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 4.333333333a + a2 = 0 + -8 4.333333333a + a2 = 0 + -8 Combine like terms: 0 + -8 = -8 4.333333333a + a2 = -8 The a term is 4.333333333a. Take half its coefficient (2.166666667). Square it (4.694444446) and add it to both sides. Add '4.694444446' to each side of the equation. 4.333333333a + 4.694444446 + a2 = -8 + 4.694444446 Reorder the terms: 4.694444446 + 4.333333333a + a2 = -8 + 4.694444446 Combine like terms: -8 + 4.694444446 = -3.305555554 4.694444446 + 4.333333333a + a2 = -3.305555554 Factor a perfect square on the left side: (a + 2.166666667)(a + 2.166666667) = -3.305555554 Can't calculate square root of the right side. The solution to this equation could not be determined.
| A(X-C)=B(X-C) | | x+x+20=30+x+100 | | 8r+2r=-8r | | y=3/4(3/4)-6 | | O=x^2-4x | | -3x+6(12-5x)=6 | | -4(3+x)+4(x-6)=-4 | | k^2-6k-9=18 | | -4x+7x-7=3(x-6)-1 | | 22+3x=2(x+3) | | -2y=-24+10x | | 25-7=18 | | 6-2(4x+1)=5x-2(2x+7) | | -5.2=m-6.8 | | -(x+7)=36 | | 5y+50-8= | | 19.6+n=24.62 | | -20=f/2 | | 2t^2-30t+0=0 | | X/-9=-14 | | 17=-6-6x-1 | | -10x-2(12-5x)=-24 | | abs(3x-5)=abs(4x-2) | | 8-(x*x+7)=-35 | | .22(x+6)=.2x+5.3 | | x/3-9/4=x/6-1/2 | | 5v^2-17v=-6 | | 1/x=4/12 | | 8a-12=4(a-5) | | 6n^2+31n+18=0 | | 70m^2-73m+20= | | 2(x-8)=9 |